San-Huang-Yi-Shen Capsule Ameliorates Diabetic Kidney Disease through Inducing PINK1/Parkin-Mediated Mitophagy and Inhibiting the Activation of NLRP3 Signaling Pathway - Hanzhou Li; Yuansong Wang; Xiuhai Su; Qinghai Wang; Shufang Zhang; Wenjuan Sun; Tianyu Zhang; Mengxue Dong; Zhaiyi Zhang; Shuquan Lv (Journal of Diabetes Research)
San-Huang-Yi-Shen capsule (SHYS) has been used in the treatment of diabetic kidney disease (DKD) in clinics. However, the mechanism of SHYS on DKD remains unclear. In this study, we used a high-fat diet combined with streptozocin (STZ) injection to establish a rat model of DKD, and different doses of SHYS were given by oral gavage to determine the therapeutic effects of SHYS on DKD. Then, we studied the effects of SHYS on PINK1/Parkin-mediated mitophagy and the activation of NLRP3 inflammasome to study the possible mechanisms of SHYS on DKD. Our result showed that SHYS could alleviate DKD through reducing the body weight loss, decreasing the levels of fasting blood glucose (FBG), and improving the renal function, insulin resistance (IR), and inhibiting inflammatory response and oxidative stress in the kidney. Moreover, transmission electron microscopy showed SHYS treatment improved the morphology of mitochondria in the kidney. In addition, western blot and immunoflourescence staining showed that SHYS treatment induced the PINK1/Parkin-mediated mitophagy and inhibited the activation of NLRP3 signaling pathway. In conclusion, our study demonstrated the therapeutic effects of SHYS on DKD. Additionally, our results indicated that SHYS promoted PINK1/Parkin-mediated mitophagy and inhibited NLRP3 inflammasome activation to improve mitochondrial injury and inflammatory responses.